Donor-acceptor random copolyesters containing perylenebisimide (PBI) and oligo(p-phenylene vinylene) (OPV) by melt condensation polymerization: energy transfer studies - Nisha, S. Kumari; Asha, S. K. (Journal of Physical Chemistry B, 2013)
Novel copolyesters consisting of oligo(p-phenylene vinylene) (OPV) as donor (D) and perylenebisimide (PBI) as acceptor (A) were synthesized by melt polycondensation. Photoinduced energy transfer and photoinduced charge separation in these polyesters were studied in solution as well as in the solid state. Selective excitation of OPV moiety resulted in the energy transfer with >90% efficiency from OPV to PBI chromophore in the solution state. The direct excitation of PBI in the D A copolyester resulted in reduced fluorescence emission of acceptor, indicating electron transfer between the D and A moieties. The effect of distance between donor and acceptor on the energy transfer efficiency from donor to acceptor was studied. Compared to a physical mixture of D and A polyesters alone, the energy transfer was 4 times more efficient in the D A copolyester, highlighting the influence of covalently linking D and A in a single polymer chain. A strong fluorescence quenching (similar to 100%) of both chromophores in solid state indicated an efficient photoinduced charge transfer after photoexcitation of either D or A. Thus, OPV-PBI main chain copolyester is an excellent system for the study of energy- and electron-transfer processes in organic semiconductor. Reactive blend of D/A copolyester was also prepared by the transesterification reaction between D and A alone copolyesters. The energy transfer efficiency from D to A moiety upon selective excitation of D chromophore in the D/A copolyester blend was similar to 4 times higher compared to a physical mixture of D and A alone copolyesters, which gave direct proof for the transesterification reaction in polyester/polyester reactive blending.

Facile one-pot reactive solution blending approach for main-chain donor-acceptor polymeric materials - Nisha, S. Kumari; Asha, S. K. (Journal of Polymer Science Part A-Polymer Chemistry, 2013)
A high-temperature solution blending process has been used to synthesize a series of copolymers incorporating varying mole ratios of perylenebisimide (PBI) into the backbone of an engineering thermoplastic polyester [poly(1,4-cyclohexylenedimethylene-1,4-cyclohexanedicarboxylate)] (PCCD). A random donor-acceptor copolymer incorporating oligo(p-phenylene vinylene) (OPV) and PBI was also synthesized. The chemical incorporation of these chromophores into PCCD was confirmed by carrying out the melt condensation using 1,4-cyclohexanedimethanol and 1,4-dimethylcyclohexane dicarboxylate with hydroxyl-functionalized PBI and OPV derivatives. Higher extent of incorporation of PBI (35 mol %) could be achieved using the blending approach retaining solubility, film-forming ability, and higher molecular weights. The PBI polymers produced using the two different approaches exhibited structural variations. The polymers formed from the solution blending approach had a semicrystalline nature with blocks of PCCD separating the PBI units, whereas those produced using the melt condensation route were amorphous polymers. This structural variation was reflected in their photophysical properties also with the reactive solution-blended polymers exhibiting higher fluorescence quantum yields. These results demonstrate the easy incorporation of suitably functionalized donor and acceptor moieties into a completely aliphatic polyester backbone to produce free-standing films of hitherto nonprocessable polymers. (C) 2012 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2013, 51, 509-524
Keywords: blending; conjugated polymers; fluorescence; PCCD; Perylenebisimide; reactive blending; transesterification

Chiral poly(L-lactic acid) driven helical self-assembly of oligo(p-phenylenevinylene) - Nisha, S. Kumari; Asha, S. K. (Journal of Materials Chemistry C, 2014)
The synthesis and self-assembly of a series of copolyesters incorporating varying mol ratios of an achiral oligo(p-phenylenevinylene) (OPV) into the backbone of a chiral poly(L-lactic acid) (PLLA) via high temperature solution blending is reported. The polymers were characterized by H-1 NMR spectroscopy and size exclusion chromatography (SEC) and their bulk properties were investigated by differential scanning calorimetry (DSC) and wide-angle X-ray diffraction (WXRD). The DSC and WXRD analyses confirmed the crystallinity and pi-pi stacking of the OPV units in the PLLA-OPV copolyester. Absorption, emission and lifetime-decay studies showed that the OPV chromophore was highly aggregated in the solid state. The solid powder samples of the copolyesters exhibited an intense, red shifted aggregate emission beyond 470 nm. Circular dichroism (CD) spectroscopy, scanning electron microscopy (SEM) and atomic force microscopy (AFM) studies revealed that the PLLA-OPV copolyester formed a self-assembled architecture, in which the helical organization of the achiral OPV segments was dictated by the chiral PLLA segments. The observed CD signal and AFM image accounted for the right-handed helical self-assembly of the OPV chromophore in the solid state. These results confirmed the effect of the chiral PLLA segment on tuning the OPV chromophore packing and supramolecular chirality in molecular aggregates. The methodology illustrated here provides opportunities for the design of a new class of hierarchical, self-assembled architectures, based on organic pi-conjugated materials and the manipulation of their optical properties.

Random copolyesters containing perylene bisimide: flexible films and fluorescent fibers - Nisha, S. Kumari; Asha, S. K. (ACS Applied Materials & Interfaces, 2014)
Random copolyesters of poly(L-lactic acid) (PLLA) and [poly-(1,4-cyclohexylenedimethylene-1,4- cyclohexanedicarboxylate)] (PCCD) incorporating varying mol ratios of perylene bisimide (PBI) were developed via a high-temperature solution-blending approach. PCCD incorporating PBI was developed by melt polycondenzation followed by a polyester-polyester transesterification reaction between PCCD PBI and PLLA. The polymers exhibited good solubility in common organic solvents and formed free-standing films, which showed bright red emission upon irradiation with ultraviolet radiation. A solid state fluorescence quantum yield of 10% was observed for this PBI based polyester, which was much higher than that reported in literature for PBI based polymers in the solid state (<1%). Strong red fluorescent nanofibers of these polymers were successfully constructed by electrospinning technique. A random copolyester incorporating donor based on oligo(p-pheneylenevinylene) (OPV) and PBI as acceptor chromophore was also synthesized and fluorescence microscopy images of the electrospun fibers of this polymer exhibited blue, green and red emission upon excitation at different wavelengths. The high temperature solution blending approach involving a high molecular weight polymer and a suitably functionalized it conjugated molecule described here is a unique method by which 1D nanostructures of a wide range of pi-conjugated chromophores could be fabricated having strong fluorescence, with the scope of application in nanoscale optoelectronics, biological devices, as well as sensing.
Keywords: flexible film; fluorescent nanofibers; luminescent film; oligo(p-phenylenevinylene); perylene bisimide